P523 Endoscopic balloon dilatation is safe and has a high success rate in patients with stricturing Crohn's disease. (25th January 2019) - Lim, E; Thai, M; Hendy, P; Alchlaihawi, M; Leong, R; Connor, S; Ng, W; Gu, B; van Langenberg, D; Thin, L; Schulberg, J; Kamm, M; et al.
Abstract: Background: Stricturing Crohn's disease (CD) is associated with significant morbidity and high rates of surgery with anastomotic strictures commonly occurring after surgery. Endoscopic balloon dilatation (EBD) may avoid or delay operative management of strictures. Methods: A retrospective audit of CD patients undergoing EBD was conducted at 11 hospitals across Australia and New Zealand. Local, prospectively maintained patient databases and procedure records were used to identify cases from June 1999 to October 2018. A stricture was defined as a narrow segment of intestine unable to be traversed with a colonoscope. Stricture length (long ≥4 cm, short <4 cm), location (ileal, ileocolonic, colonic, anorectal) and type (anastomotic vs. de novo) were collected from endoscopy reports. Dates of surgeries and follow-up were obtained from medical records. Technical success was defined as the ability to traverse the stricture following dilatation. Baseline smoking status, Montreal phenotype and medications for CD were also documented. Results: A total of 236 patients with stricturing CD were identified (120 male, median age 48 [IQR: 10], 29% ileal, 12% colonic, 59% ileocolonic). A total of 620 dilatation procedures (303 for anastomotic strictures, 312 for de novo strictures, 5 unknown) were performed (median 2 per patient) with 428 (69%) on short strictures, 109 (18%) on long strictures, and 83 (13%) of unknown length. Balloon dilation diameter was 8 mm–20 mm (median 15 mm). Technical success was achieved in 433 (84%) of dilatations, and was significantly higher for short vs. long strictures (93% vs. 66%, p < 0.001). Technical success was lower in ileal strictures (72%) than colonic or ileocolonic strictures (89% and 85%, respectively, p = 0.002). End-to-end anastomosis had a numerically higher success rate (85% vs. 75%, p = 0.19). During the median follow-up time from first EBD to last review or surgery (50 months, [IQR: 30]), 55 patients (23%) required surgery for stricturing CD post-dilatation. The median time to surgery following the last dilatation was 8 months (range 0–90 months). Complications of EBD included 3 cases of perforation and two cases of aspiration. There was no major bleeding or procedure-related mortality identified. Conclusions: In one of the largest analyses of EBD for CD strictures, EBD is found to be a safe procedure with a high technical success rate overall. The highest success was observed in strictures less than 4 cm in length and non-ileal in location. EBD may be an effective strategy for avoiding surgery in stricturing Crohn's disease and post-operative anastomotic strictures.